Covid-19 dan Dampaknya Terhadap Kinerja Bank BUMN di Indonesia - Mar'a Elthaf Ilahiyah; Miguel Angel Esquivias Padilla; Dian Palupi (Esensi: Jurnal Bisnis dan Manajemen, 2021)
Covid-19 has increased the risk of financial institutions. As countries struggle to strengthen economic activity and provide various fiscal stimuli to facilitate liquidity in the market, this study questions whether national banks are still in a healthy condition to face uncertainties in the market. This study applies the RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) approach to assess the performance of state-owned banks in Indonesia during the new normal period since June 2020 (quarter II and III). Based on the analysis and discussion of this study, it can be concluded that the condition of state-owned banking in Indonesia during the new normal period was still healthy. Bank risk level remains at a safe level. Bank made huge profits and fixed capital is still at a healthy level. Thus, state-owned banks remain competitive and handle risk well. This is supported by the existence of stimulus assistance from the government in the form of the Countercyclical Policy.Cara Mengutip:Ilahiyah, M. E., Padilla, M. A. E., & Palupi, D. (2021). Covid-19 dan Dampaknya Terhadap Kinerja Bank BUMN di Indonesia. Esensi: Jurnal Bisnis dan Manajemen, 11(1), xx-xx. https://doi.org/10.15408/ess.v11i1.19297.